(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In many cases, the assessment and analysis of ecological risks is a complicated task, which is first of all related to obtaining reliable initial information. As a rule, ecological risks are due to unrepeated unique situations; from this it follows that sufficient statistical data on whose basis reliable evaluation of specific risks is made, are not available. On the other hand, unfavourable impacts on the external environment can affect the components of an ecosystem differently. The complexity of correlations among the components of an ecosystem significantly complicates an analysis of possible impacts on the components of a specific system.When statistical data are missing or insufficient, experts who perform the required assessment on the basis of their knowledge and experience but often also using their intuition, are the only source of initial data. Here, however, the problem of reliability of expert evaluations arises. If other sources of information are missing, we have to accept subjective evaluations of experts as a basis, without an opportunity to evaluate the degree of their confidence.In this kind of situation, it seems to be validated to introduce the extent of uncertainty into the evaluations of parameters of ecological risks. This can be accomplished by using fuzzy initial evaluations. This paper focuses on the concept of fuzzy random events and shows favourable chances of using that concept in the assessment and analysis of ecological risks.